Ontological formation of the Otaku subculture and subjects in Bangladesh - Yameen, Syed Ibtesham (BRAC University, 2017)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2016.